A flexible, high-strength, conductive shape memory composite fabric based on continuous carbon fiber/polyurethane yarn. (16th July 2020) - Sun, Ya; Chen, Haijia; Yin, Hao; Sun, Baozhong; Gu, Bohong; Zhang, Wei
Abstract: Shape memory textiles, as an active stimulus-responsive smart material, play an important role in sensors and actuators, which have tremendous potential for various fields. High mechanical performance and multiple-stimulus responses are urgently demanded in practical applications. In this work, a conductive composite yarn of continuous carbon fiber coated shape memory polyurethane by melt-extrusion method was fabricated and woven into fabrics. The microstructure and related influence factors on the mechanical property as well as shape memory behavior all have been characterized. Based on the advantages of carbon fiber and polyurethane, the full-textile structured composite fabric revealed remarkable shape memory behavior under thermal and electrical stimulation and possessed excellent mechanical property as well as flexible deformations ability, which makes it promising to apply in wearable smart textiles, biomedicine, aerospace, and other fields.